Spatiotemporal variations of carbon emissions in digital economy: evidence from China - Xia, Yihan; Ji, Kaiwen; Ren, Chenhui; Jiang, Liangshun (Frontiers in Environmental Science, 2025)
The last few decades witnessed the tremendous growth of Chinese digital economy. How to calculate and estimate the carbon footprints of this rising economic formation, naturally becomes an issue. Based on the provincial panel from China spanning 2016 to 2021, we conduct an in-depth analysis of the spatial characteristics of carbon emissions in China’s digital economy and empirically investigates the driving forces of the spatial differentiation. The results indicate that carbon emissions show rapid growth and a distinct “T-shaped” spatial pattern, with high-emission areas expanding and carbon footprints becoming more dispersed. The spatial variation is driven by six key dimensions with strong interactive effects. By constructing a new emission measurement framework, this study offers spatiotemporal insights into digital carbon footprints, providing relevant implications for enhancing the sustainability of the digital industry and supporting global carbon reduction goals.